Complementary Strand MicroRNAs Mediate Acquisition of Metastatic Potential in Colonic Adenocarcinoma - Chen, Dung-Tsa (J Gastrointest Surg, 2012)
BACKGROUND AND AIMS: Altered expression of specific microRNAs (miRNA) is known to occur during colorectal carcinogenesis. However, little is known about the genome-wide alterations in miRNA expression during the neoplastic progression of primary colorectal cancers. METHODS: Using a miRNA array platform, we simultaneously evaluated the expression of 668 miRNA in primary colonic adenocarcinomas. Prediction analysis for microarrays (PAM) was used to identify differentially expressed miRNA. Biological functions of selected miRNA were evaluated with in vitro invasion assays. RESULTS: Primary fresh frozen tissues from 65 patients (40 male and 25 female) with a mean age 65 +/− 13 years and with AJCC Stages I (n=7), II (n=22), III (n=18) and IV (n=18) colon cancers, underwent RNA extraction and miRNA array analysis. We identified a seven-miRNA expression signature that differentiated Stage I and Stage IV primary colon cancers. We then demonstrated this signature was able to discriminate between Stage II and III primary colon cancers. Interestingly 6 of the 7 differentially expressed miRNA were downregulated in association with the development of metastases, and all 7 miRNA were complementary strand miRNA*. We transfected HCT-116, a highly invasive colon cancer cell line, with corresponding downregulated miRNA* and demonstrated that overexpression of 3 of the 6 miRNA* (miR200c*, miR143*, and miR424*) significantly abrogated invasive potential. CONCLUSION: We have identified a seven-miRNA* signature that is associated with metastatic potential in the primary tumor. Forced over-expression of 3 of the 6 identified miRNA* resulted in an attenuation of in vitro invasion, suggesting direct tumor suppressive function and further supporting the biological importance of complementary strand miRNA*.